CHEMICAL COMPOSITIONS OF PINE RESIN, ROSIN AND TURPENTINE OIL FROM WEST JAVA - Wiyono, Bambang; Tachibana, Sanro; Tinambunan, Djaban (Indonesian Journal of Forestry Research, 2006)
This study was conducted to identify chemical composition of merkus pine resin, rosin and turpentine oil. Initially, pine resin was separated into neutral and acidic fractions with an aqueous 4% sodium hydroxide solution. After methylation, the fraction containing turpentine oil and rosin were analyzed by gas chromatography (GC), and gas chromatograph mass spectrometry (GC-MS), respectively. The neutral fraction of pine resin and turpentine oil mainly consisted of a-pinene, D-3-carene and b-pinene. Based on mass spectral comparison, the major constituents of the acidic fraction and rosin were identified as sandaracopimaric acid, isopimaric acid, palustric acid, dehydroabietic acid, abietic acid, neoabietic acid, and merkusic acid. The major component of the acidic fractions was palustric acid, while that of rosin was abietic acid. Using TC (tough column) 1 and TC 5 columns, levopimaric acid could not be separated from rosin or acidic fraction of pine resin of Indonesian Pinus merkusii.